New combination and typification of Tanacetum parthenium var. flosculosum (asteraceae) and its first record from turkey - Barış Bani; Pelin Acar (National Library of Serbia, 2023)
In this study, a discoid capitulate variety of Tanacetum parthenium was recorded for the first time in Turkey. Additionally, the new combination of the name is given as Tanacetum parthenium var. flosculosum. Moreover, the varietal name was neotypified with material from Vaillants? collection at P.
Keywords: neotype; feverfew; new record; nomenclatural change; QK900-989; asia; Plant ecology